Midwifery Care for Pregnant Women in Mrs. P G: III P: II A: 0 With Mild Anemia at Maternity Clinic Dewi Sundari, Amd.Keb Kota Tanjung Balai - Delimayani, Delimayani; Murniati, Murniati (Institute of Accounting Research and Novation (IARN), 2023)
Anemia is a condition where there is a reduction in red blood cells (erythrocytes) in the blood circulation or hemoglobin mass so that they are unable to fulfill their function as a carrier of oxygen throughout the tissues. Anemia in pregnancy is caused by iron deficiency, reaching approximately 95%. Globally, the prevalence of anemia in pregnant women throughout the world is 41.8%. The prevalence of anemia in pregnant women in Asia is estimated at 48.2%, Africa 57.1%, America 24.1% and Europe 25.1%. The prevalence of anemia in pregnant women in Indonesia is 70% and the prevalence of anemia in South Kalimantan is 10.9%. Anemia in pregnant women is associated with increased births of low birth weight (LBW) babies, prematurity, maternal and child deaths and infectious diseases. Iron deficiency anemia in the mother can affect the growth and development of the fetus/baby during pregnancy and afterward.